Moringa oleifera Supplemented Diets Prevented Nickel-Induced Nephrotoxicity in Wistar Rats - O. S. Adeyemi; T. C. Elebiyo (Journal of Nutrition and Metabolism)
Background. The Moringa oleifera plant has been implicated for several therapeutic potentials. Objective. To evaluate whether addition of M. oleifera to diet has protective effect against nickel-induced nephrotoxicity in rats. Methodology. Male Wistar rats were assigned into six groups of five. The rats were given oral exposure to 20 mg/kg nickel sulphate (NiSO4) in normal saline and sustained on either normal diet or diets supplemented with Moringa oleifera at different concentrations for 21 days. 24 hours after cessation of treatments, all animals were sacrificed under slight anesthesia. The blood and kidney samples were collected for biochemical and histopathology analyses, respectively. Results. NiSO4 exposure reduced the kidney-to-body weight ratio in rats and caused significant elevation in the levels of plasma creatinine, urea, and potassium. Also, the plasma level of sodium was decreased by NiSO4 exposure. However, addition of M. oleifera to diets averted the nickel-induced alteration to the level of creatinine and urea. The histopathology revealed damaged renal tubules and glomerular walls caused by NiSO4 exposure. In contrast, the damages were ameliorated by the M. oleifera supplemented diets. Conclusion. The addition of M. oleifera to diet afforded significant protection against nickel-induced nephrotoxicity.